PENERAPAN STRATEGI GENIUS LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI IPA SMA NEGERI 3 PEKANBARU - Humaidatul Fikriah; Johni Azmi; Sri Haryati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The implementation of Genius Learning Strategy aims to know the increase of student achievement on the subject Solubility and Constant Solubility Product in class XI SMAN 3 Pekanbaru. This research is experimental research with randomized control group pretest-postest design. The sample of this research were students of class XI IPA 4 as the experimental research and students of class XI IPA 1 as a control class that has been randomly selected after a test of normally and homogenity test. Experiment class is a class that is applied Genius Learning strategy while the control class without applied Genius Learning strategy. Data analysis technique used is t test. Based on analysis of the data obtained tcount > ttable is 2,75>1,66, it is mean that the apllication of Genius Learning strategy can improved students learning achievement on the subject solubility and constant solubility product in class XI SMAN 3 Pekanbaru. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,70 and at control class was medium category with N-gain normalized is 0,56.Keywords : Genius learning, Learning Achievement, Solubility and Constant Solubility Product(Ksp)